기내 검정법을 이용한 국내 과수 화상병 방제제 선발 - 이민수(Min Su Lee); 이인경(Ingyeong Lee); 김삼규(Sam Kyu Kim); 오창식(Chang-Sik Oh); 박덕환(Duck Hwan Park) (Sigmulbyeong yeon'gu, 2018)
Since fire blight disease on apple and pear was produced in Korea in 2015, there were no registered chemicals to control against this disease. Instead, several antibacterial chemicals that were registered for other bacterial diseases such as soft rot and bacterial spot have been authorized by Rural Development Administration (RDA). However, these chemicals are not tested efficacy for fire blight disease except damage by those treatments on apple and pear in Korea. Thus, we evaluated efficiency using in vitro and in planta assays of antibacterial chemicals such as antibiotics and copper compounds including kasugamycin, oxytetracycline, oxolinic acid and streptomycin, and copper hydroxide, copper sulfate, oxine copper and tribasic copper sulfate, respectively. We also tested two kinds of biological agents. As expected, significant antibacterial effect was observed in vitro test of both antibiotics and copper-based chemicals. In planta test based on disease severity including ooze and water-soaked formation on immature pears, bacterial populations on blooms, and blight lesion formation in artificially inoculated shoots, kasugamycin, oxytetracycline and streptomycin have been shown the most efficiency among tested antibiotics. Four copper-based chemicals tested in this study, control effects are little bit lower than agricultural antibiotics but they seem to be available to use in terms of winter season. Biocontrol agents were also shown possibility to treat in eco-friendly farms. In addition, there are no antibiotic resistance genes in Korean isolates against antibiotics, which were selected for suppression of fire blight in this study. 국내 과수 화상병은 2015년 사과 및 배에서 발생하여 큰 피해를 주고 있으나, 이에 대한 적절한 방제제는 등록되어 있지 않다. 다만 농촌진흥청은 무름병과 세균점무늬병 등 다른 식물세균병해에 등록되어 있는 살세균제들을 직권등록 시켜놓은 상태이다. 그러나 직권등록이란, 약효는 보증하지 않으면서 약해만을 보증하는 제도로, 국내에서 과수 화상병이 지속적으로 발생되고 있는 상황에서는 적절한 방제제를 선발하는 것이 요구되어지기에 본 연구를 수행하였다. 직권등록 국내 과수 화상병 방제제 중, 각각 4종의 농용항생제와 구리 합성 화학물 그리고 생물학적 방제제 2종에 대한 기내 검정법을 통하여 국내 과수 화상병원세균 억제 및 병징확산 억제효과를 검증하였다. Kasugamycin, Oxytetracycline 및 streptomycin의 항생제는 효과가 우수하였으며, oxolinic acid는 꽃에서의 억제효과는 우수하였지만 신초 및 미성숙과 기내검정에서는 다소 효과가 감소하였다. 4종의 구리 합성 화학물은 항생제만큼의 억제효과는 나타내지 않았지만, 사용가능한 수준으로 조사되었다. 또한 2종의 생물적 방제제는 처리시기 등을고려할 경우, 친환경 재배지에서는 사용 가능할 것으로 판단되었다. 한편 국내 과수 화상병원세균은 선발 방제제 중 항생제 저항성 유전자들을 가지고 있지 않고,화분매개충에 대한 영향도 없는 것으로 조사되었다.